2016
DOI: 10.25100/socolen.v42i1.6666
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de aislamientos nativos de Beauveria bassiana y su patogenicidad hacia Hypothenemus hampei, en Tabasco, México

Abstract: Con la finalidad de contar en Tabasco, México con aislamientos nativos de Beauveria bassiana con potencial de control de Hypothenemus hampei, 12 cepas se aislaron y caracterizaron según variables fisiológicas y patogénicas. El crecimiento micelial (CM), la velocidad de germinación y la producción de conidios (PdC) en agar-dextrosa de Sabouraud + 0,1% de extracto de levadura (ADS+EL), son las variables fisiológicas consideradas y evaluadas a 25, 30 y 35 °C. Además, se evaluó la PdC en arroz a 25 °C. Hubo difere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
3
6
0
1
Order By: Relevance
“…with 3.83 × 10 8 conidia/mL −1 . Te conidia production obtained by B. bassiana and B. peruviensis is close to values reported by Torres et al [29] for native strains of B. bassiana in Tabasco, Mexico. However, the conidia production obtained with Metarhizium sp.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…with 3.83 × 10 8 conidia/mL −1 . Te conidia production obtained by B. bassiana and B. peruviensis is close to values reported by Torres et al [29] for native strains of B. bassiana in Tabasco, Mexico. However, the conidia production obtained with Metarhizium sp.…”
Section: Resultssupporting
confidence: 89%
“…Te mortality caused by B. bassiana 1 × 10 9 and B. bassiana 1 × 10 7 on H. hampei agrees with Bastidas et al [35] who reported 90% mortality of H. hampei caused by B. bassiana strains at times from 106 to 129 h. Likewise, Torres et al [29] reported 100% mortality of H. hampei by native strains of B. bassiana in Mexico. However, these authors reported mortality at 144 h and a concentration of 1 × 10 7 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Fungal strains were isolated from infected coffee borers ( Hypothenemus hampei ) obtained from infected coffee berries according to Gerónimo-Torres et al (2016). They were collected during July and August 2017 from three districts in the province of Rodriguez de Mendoza, Amazonas, Peru (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…According to Mota et al (2017), fungal species B. bassiana used in synthetic tissues surface treatment, at concentration of 5.44 × 10 8 .cm -2 , recorded 88.5% H. hampei mortality rate after five seconds of exposure to it. Immersion based studies conducted with different B. bassiana isolates against H. hampei recorded up to 100% insect mortality rate, Gerónimo-Torres et al (2016); Posada-Flórez (2008).…”
Section: Introductionmentioning
confidence: 99%